Wear failure analysis of suction valve for high pressure and large flow water hydraulic plunger pump. (April 2022) - Dong, Jie; Deng, Yipan; Cao, Wenbin; Wang, Zhongkai; Ma, Wensheng; Wu, Defa; Ji, Hong; Liu, Yinshui
Highlights: The failure mode of large-flow valve is different from that of small-flow valve. Rotation and impact are the key factors of wear failure of large flow valve plate. The failure of the valve plate is the mixed wear dominated by adhesive wear. The improved valve plate materials obviously reduce the wear of sealing surface. Abstract: The failure mechanism of suction valve in high pressure and large flow water hydraulic plunger pump used in coal mine is studied. Previous studies believe that in traditional plunger pump with low pressure and small flow, the impact caused by the dynamic contact between the valve plate and the valve seat is the main reason for the performance deterioration of suction valve. However, in the practical use of high-pressure and large-flow hydraulic plunger pump, it is found that there are signs of rotating wear and material loss on the sealing surface of the suction valve plate. In order to explain the premature failure of the valve, the mathematical model of the force and movement of the valve plate during the suction process of the high-pressure and large-flow hydraulic plunger pump is established. Three-dimensional computational fluid dynamics (CFD) method and nonlinear finite element method are used to numerically analyze the operation process and dangerous conditions of the valve plate. The results show that under the action of the uneven flow field, the combination effects of low speed rotation and heavy load during closing process is the key factor causing material loss. According to the microstructure and elemental composition of the worn surface, the specific wear failure mechanism is determined, and the effectiveness of the numerical method is verified. Finally, the improved valve plate materials are proposed. The field test of high pressure and large flow pump proves that the wear of the valve plate is significantly reduced after the improvement.